Ponggawaian Problems in Creating Job Opportunities in the Maritime Sector - Mallebi, We Ati Mega Daeng; Demmallino, Eymal B.; Nadja, Rahmawaty A.; Salman, Darmawan; Summase, Idris; Thamrin, Muh (International Journal Papier Advance and Scientific Review, 2023)
The success of maritime development must be felt by the surrounding coastal communities, most of whom work as fishermen and have low education, so it is necessary to pay attention to efforts to improve the standard of living of the people in coastal areas and overcome the problem of unemployment. The fishing community group which is a Bugis-Makassar fisherman organization has been formed for generations. In general, this Bugis and Makassar fishing organization is referred to as Ponggawa-Sawi with all the problems in it. The purpose of this research is to find out how the problem of professionalism is in job creation. The research method used is qualitative with data collection using the in-depth interview method with key respondents and analyzed using the APPAS method. The results of the study show that 1) the problem of employment in creating employment opportunities has been going on for a long time, both in a structured way, in this case mustard (workers) have a low bargaining position because there are not many alternative job opportunities available; 2) business owners have problems in terms of lacking managerial ability so that business results are less than optimal. The use of the APPAS method recommends several things related to the problems that occur, namely 1) make a clear work contract for workers (sawi); 2) carry out training or assistance related to increasing the managerial capabilities of business owners.